Chatbot Deteksi Awal Gangguan Kecemasan Menggunakan Dialogflow - Rahmat Rizki Hidayat; Muhammad Fikry; Yusra Yusra (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Nowadays, anxiety disorders are experienced by many individuals, making a significant impact on one's quality of life. Some people are unaware of the symptoms of anxiety disorders, making anxiety disorders trivial. This situation can cause serious physical and emotional discomfort, in some cases, leading to more severe impacts if not treated appropriately. One of the first steps in overcoming anxiety disorders is early detection. The earlier the disorder is detected, the better the chances of providing effective treatment and reducing its impact. The development of artificial intelligence technology has opened up new opportunities to address this problem. This research proposes an innovation in the form of a chatbot. The purpose of this study is to determine the feasibility and acceptability of a chatbot to identify and provide information related to symptoms of anxiety disorders. The research methodology includes Data Collection, conversation formation, model formation, implementation using Dialogflow, testing and results. The results of UAT testing on respondents consisting of students and psychologists obtained results of 84% and 74%, respectively.